Optimal Marketing Strategies for Distribution Channels of Organic Agricultural Products in Chiang Mai Province - สุภาพันธ์, พัชรินทร์; คงธนจารุอนันต์, รภัสสรณ์; บุญมาก, จาเนียร; อวิโรธนานนท์, ทัดพงศ์; อินธนู, พัชรี (Parichart Journal, 2017)
The objective of this study was to analyze optimal marketing strategies for distribution channels of organic agricultural products according to marketing mix theory with multinomial logit model. Data were collected in the form of interviews with questionnaires from 2,450 consumers who bought organic agricultural products by means of purposive random sampling of 25 districts in Chiang Mai province. It could be concluded that an increased probability of the products distributed in the safe markets where the organic agricultural products were mutually sold with safe agricultural products, the particular safe markets, and the particular organic markets should focus on the product, promotion, and price marketing strategies, respectively. Moreover, the product and promotion strategies were related to safety and free from chemical residue, marketing promotion under discounting, changing, distributing, adding, or testing, and advertisement and public relations of private agencies corresponding with the organic agricultural products. They should be carefully processed since these marketing strategies resulted in the possibility of a decrease for the products distributed in general markets. It indicated that the different sale between agricultural and organic agricultural products influenced demand decision of consumers. Therefore, the optimal marketing strategies for distribution in each marketing channel led to the trade advantage